Análisis e interpretación financiero, liquidez y rentabilidad como herramienta para la evaluación de la gestión empresarial - Jordán Guillén, Christian Mauricio (2015)
The Finances Analysis and its interpretation is compulsory to examine the economic development of the enterprises, because it detects difficulties and allows us to take corrective actions to improve corporate management. The objective of this paper is to determinate the importance of the analysis and its interpretation, of financial currency and profitability as a tool for the evaluation of the management in the company Conarcas Ltda. This is a documental and quantitative paper, based on the review of scientific articles, such as Castaños Ríos, Carlos Eduardo; Arias Pérez, José Enrrique, (2013) Martín Granados, Fontalvo Herrera, Tomás; De la Hoz Granadillo, Efraín; Vergara, Juan Carlos (2014) among others. The fianacial analysis throug the liquity and profitability, performs calculations that allow the employer knowing which is the situation of your business. It is considered that a company not only imports the profitability, but that is happening whit this, watch the evolution. The financial analysis based on measurement is a corect tool for the evaluation of the management, it’s a key to all activity evironment development by an entity, that dermines the present situation and glanced through future forecast, therefore it is recommended that your develoyment responsible and have a trained person to carry out this analysis.